Manajemen Strategik Berbasis Data dalam Peningkatan Mutu Sekolah: Systematic Literature Review - Fitriyana Fitriyana; Junaina Junaina; Merita Diana; Nirva Diana; Aan Komariah; Badrudin Badrudin (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Data-based strategic management has become an essential approach for school improvement because schools are increasingly expected to plan, implement, and evaluate quality enhancement programs through credible evidence rather than administrative intuition. This Systematic Literature Review aims to synthesize studies on data-based strategic management in school quality improvement, identify how data are used across strategic management cycles, examine enabling and constraining factors, and formulate a contextual conceptual model for schools. The review adapted PRISMA 2020 and PRISMA-S guidelines. Searches were conducted across Scopus, Web of Science, ERIC, DOAJ, Crossref, Google Scholar, Garuda, and official Indonesian education policy sources using English and Indonesian keywords related to data-driven decision making, strategic management, school improvement, Rapor Pendidikan, and Perencanaan Berbasis Data. From 773 initially identified records, 35 core documents met the inclusion criteria and were analyzed thematically. The findings indicate that data-based strategic management involves quality diagnosis, data interpretation, strategy articulation, program implementation, impact evaluation, and continuous correction. Key enabling factors include principal leadership, teacher data literacy, collaborative data culture, data validity, digital infrastructure, and policy support. Major barriers include administrative data use, limited analytical capacity, fragmented information systems, and organizational resistance. The study contributes a DIALEKTIK-DATA model to strengthen evidence-informed school governance and continuous quality improvement.